Supplantation of the superficial branch of the radial nerve by the lateral antebrachial cutaneous nerve (2013)
Introduction: the sensitive innervation of the dorsum of the hand comes mainly from the superfcial branch of the radial nerve, but this territory can be assumed by  the  lateral antebrachial cutaneous nerve. Objective:  to describe a  rare variation of  the  lateral cutaneous nerve of the forearm found in the cadaver lab of the Department of Morphology, at the Universidad del Valle in Cali, Colombia. Materials and Methods: male colombian cadaver, dissected by medical  students. Results:  the  superfcial branch of  the  radial nerve was absent and  its sensory territory was totally assumed by the  lateral antebrachial cutaneous nerve, which  in the dorsum of the hand divided  in the digital dorsal nerves  for  the  thumb,  index  and middle fngers and  the  lateral half of  the  fourth digit. Discussion and Conclusion: considering the clinical and surgical  implications that the distribution of a nerve can have,  it  is  important to know precisely  its normal anatomy and its possible variations, and direct them to the knowledge about the morphological characteristics of each population. (MÉD.UIS.2013;26(3):51-55)